Effects of Previous or Synchronous Non-Muscle Invasive Bladder Cancer on Clinical Results after Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma: A Multi-Institutional Study - Kim, Bup Wan; Ha, Yun-Sok; Lee, Jun Nyung; Kim, Hyun Tae; Kim, Tae-Hwan; Lee, Jung Keun; Byun, Seok-Soo; Choi, Young Deuk; Kang, Ho Won; Yun, Seok-Joong; Kim, Wun-Jae; Kwon, Young Suk; et al. (Urology Journal, 2015)
Purpose: To evaluate the effects of the presence of previous or synchronous non-muscle invasive bladder cancer (NMIBC) on the oncologic outcomes of radical nephroureterectomy in patients with upper tract urothelial carcinoma (UTUC). Materials and Methods: In total, 505 patients with UTUC were enrolled from four different institutions. The clinicopathologic parameters of patients with and without previous or synchronous NMIBC were compared, and Kaplan-Meier estimates and multivariate Cox regression analyses were performed. Results: The median follow-up period was 38.4 months. In all, 408 patients had primary UTUC, 45 (8.9%) had a history of NMIBC, 59 (11.7%) had concomitant bladder cancer, and seven (1.4%) had experienced both. Tumors in patients with associated NMIBC were more commonly multifocal (P = .001) and associated with surgical margin positivity (P = .001). Kaplan-Meier estimates revealed that previous or synchronous NMIBC was significantly associated with bladder recurrence (P < .001) and locoregional recurrence/ distant metastasis (P = .008). A multivariate Cox regression model identified previous or synchronous NMIBC as an independent predictor of bladder recurrence (P < .001). However, the presence of previous or synchronous NMIBC was not a prognostic indicator of locoregional recurrence/distant metastasis. Conclusion: In patients with UTUC, previous or synchronous NMIBC was significantly associated with an increased risk of cancer recurrences in the bladder after radical nephroureterectomy. The present findings suggest that a close monitoring should be required for the patients with previous or concomitant NMIBC.